Work Readiness: The Effeck of Teacher Competence, Work Skills and Entrepreneurial Attitude - Agussalim, Agussalim; Said, Sitaman; Wahyuni, Wahyuni; Burhanuddin, Burhanuddin; Yani, Ahmad (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
This research aims to analyze the influence of teacher competence, and work skills on work readiness with entrepreneurial attitude as an intervening variable. The research sample was 198 students who graduated from SMK Negeri in Bima City, between 2017-2022. The research instrument is a questionnaire developed from each exogenous and endogenous variable in this research. Data were analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM). The research results show that teacher competence has a significant and positive influence on students' work readiness, but does not have an indirect influence on work readiness through entrepreneurial attitudes as an intervening variable. Work skills have a significant direct and indirect influence on work readiness with entrepreneurial attitude as an intervening variable. Meanwhile, entrepreneurial attitudes do not have a significant effect on students' work readiness. The implications of this research need to be strengthened by increasing teacher competence and work skills so that students have work readiness after graduating from school.